Characterization and Biological Properties of Dry Fermented Product (Jameed) Manufactured from Cow Milk: Comparison of Sun and Freeze Drying. Issue 3 (17th February 2014) - Alu'datt, Muhammad H.; Al‐Rabadi, Ghaid J.; Al‐Ismail, Khaild M.; Althnaibat, Rami M.; Ereifej, Khalil; Rababah, Taha; Alhamad, Mohammad N.; Torley, Peter J.
<x xml:space="preserve">Abstract</x> The effect of sun or freeze drying techniques on the chemical, nutritional and biological properties of either unsalted or salted cow milk jameed was studied. The products were characterized for: yield, composition, fatty acid profile and bioactivity. The highest yield (51.38%) was obtained in salted sun‐dried jameed. New major bands were detected in unsalted jameed prepared by either sun drying or freeze drying from cow milk compared with salted jameed prepared by either sun drying or freeze drying. Preparation of unsalted sun‐dried jameed increased the protein (63.5 g/100 g) and carbohydrate (29.5 g/100 g) contents, and reduced the fat (2.7 g/100 g) and ash (4.4 g/100 g) contents. Optimum color values were found in sun‐dried salted jameed from cow milk. Preparation of jameed either with use or without use of salt treatments in sun drying techniques of cow milk may increase the content of short chain fatty acids. Practical Applications Jameed is a sun‐dried fermented dairy product. This study concluded that the freeze drying technique improved the quality, physical, chemical, biological and nutritional properties of jameed, and recommended that jameed be used commercially as food ingredient in foods and their products. Economically, the freeze drying technique is more expensive as compared with the sun drying technique.